Phenotypic variability evaluation and genetic variation in F2 intraspecific hybrids of cucumber (Cucumis sativus L.) using retrotransposon-based markers - AGUS BUDI SETIAWAN; QONITA AULIA ZAHIDAH; DIAS NABILA KALTSUM; AZIZ PURWANTORO (Society for Indonesian Biodiversity, 2023)
Abstract. Setiawan AB, Zahidah QA, Kaltsum DN, Purwantoro A. 2023. Phenotypic variability evaluation and genetic variation in F2 intraspecific hybrids of cucumber (Cucumis sativus L.) using retrotransposon-based markers. Biodiversitas 24: 2596-2604. Cucumber (Cucumis sativus L.) has a narrow genetic base compared to other Cucumis species. The genetic base of the cucumber can be improved by crossing two distantly related cultivars from different geographical locations. This study aimed to evaluate phenotypic variability and investigate genetic variation of F2 cucumber population using two retrotransposon-based markers, namely Inter Retrotransposon Amplified Polymorphism (IRAP)andInter-SINE Amplified Polymorphism(ISAP). Two parental lines and the selected 59 genotypes from F2 population were subjected to PCR analysis for DNA profiling. The phenotypic variation of F2 genotypes revealed significant diversity in fruit weight, fruit diameter, fruit radian, pedicel length, fruit length, and fruit ratio (length-diameter). The genetic variation of the F2 hybrids was successfully detected and discriminated by IRAP and ISAP markers. Both IRAP and ISAP markers showed high heterozygosity ranged from 0.4021 to 0.4997, with an average of 0.4649 and moderate polymorphic information content ranged from 0.3489 to 0.3929 with an average of 0.3648. Cluster analysis showed that the F2 population and parental lines were grouped into two major clusters with a similarity coefficient ranged from 0.67 to 0.96. These findings imply that the F2 population is highly segregated and can be utilized to create new cultivars of cucumber.